A case study on generation mechanisms of a sporadic sodium layer above Tromsø (69.6° N) during a night of high auroral activity - Takahashi, Toru; Nozawa, Satonaori; Tsuda, Takuo T.; Ogawa, Yasunobu; Saito, Norihito; Hidemori, Takehiro; Kawahara, Takuya D.; Hall, Chris; Fujiwara, Hitoshi; Matuura, Nobuo; Brekke, Asgeir; Tsutsumi, Masaki; et al. (Annales Geophysicae, 2015)
Published version. Source at http://doi.org/10.5194/angeo-33-941-2015 . We have quantitatively evaluated generation mechanisms of a sporadic sodium layer (SSL) based on observational data obtained by multiple instruments at a high-latitude station: Ramfjordmoen, Tromsø, Norway (69.6° N, 19.2° E). The sodium lidar observed an SSL at 21:18 UT on 22 January 2012. The SSL was observed for 18 min, with a maximum sodium density of about 1.9 × 1010 m−3 at 93 km with a 1.1 km thickness. The European Incoherent Scatter (EISCAT) UHF radar observed a sporadic E layer (Es layer) above 90 km from 20:00 to 23:00 UT. After 20:00 UT, the Es layer gradually descended and reached 94 km at 21:18 UT when the SSL appeared at the same altitude. In this event, considering the abundance of sodium ions (10 % or less), the Es layer could provide only about 37 % or less of the sodium atoms to the SSL. We have investigated a temporal development of the normal sodium ion layer with a consideration of chemical reactions and the effect of the (southwestward) electric field using observational values of the neutral temperature, electron density, horizontal neutral wind, and electric field. This calculation has shown that those processes, including contributions of the Es layer, would provide about 88 % of sodium atoms of the SSL. The effects of meteor absorption and auroral particle sputtering appear to be less important. Therefore, we have concluded that the major source of the SSL was sodium ions in a normal sodium ion layer. Two processes – namely the downward transportation of sodium ions from a normal sodium ion layer due to the electric field and the additional supply of sodium ions from the Es layer under relatively high electron density conditions (i.e., in the Es layer) – played a major role in generating the SSL in this event. Furthermore, we have found that the SSL was located in a lower-temperature region and that the temperature inside the SSL did not show any remarkable temperature enhancements.